Recurrent HELLP Syndrome at 22 Weeks of Gestation - Peter Kascak; Milos Paskala; Peter Antal; Radovan Gajdosik (Case Reports in Obstetrics and Gynecology)
We describe a case of a woman who presented with HELLP syndrome in two subsequent pregnancies (age 36 and 40), at gestational age of 22 weeks in both pregnancies with a rapid onset and progression. She presented with characteristic clinical symptoms and laboratory findings. Both pregnancies were delivered by caesarean sections due to deterioration in the mother’s condition, although neither pregnancy progressed into the 1st stage of the syndrome according to Mississippi classification. This case highlights the admittedly rare but serious condition of recurring HELLP syndrome at a gestational age before the limit of viability of the fetus. In such situations, pregnancy termination should be considered to minimise risk to the mother’s life and health.